(untitled) (Baghdad Science Journal, 2025)
This study included isolation of some active materials from Curcuma longa such as tannins, saponins and volatile oils with percentage of 59%, 31%, and 9% respectively. Also the study included the determination of minerals in Curcuma longa such as " Na, Ca and K" using Flame photometer. The concentrations of these minerals were (14 ppm),(10 ppm) and )76 ppm) respectively. The anti-bacterial activity study was performed for the active materials isolated from Curcuma longa against two genus of pathogenic bacteria, Escherichia Coli and Staphylococcus aurous by using agar-well diffusion method. It appeared from this study that all of the extraction have inhibitory effect on bacteria was used. The inhibition zone diameter varies with the type of active compound, its concentration and the types of bacteria. The results obtained were analyzed statistically way (one way ANOVA) she stated results that alcoholic extract warm has had the greatest influence on the ratio of the number of cells developing and the effect was significantly (P